1989
DOI: 10.1152/jappl.1989.66.6.2710
|View full text |Cite
|
Sign up to set email alerts
|

Threshold for muscle lactate accumulation during progressive exercise

Abstract: The purpose of this study was to investigate the relationship between muscle and blood lactate concentrations during progressive exercise. Seven endurance-trained male college students performed three incremental bicycle ergometer exercise tests. The first two tests (tests I and II) were identical and consisted of 3-min stage durations with 2-min rest intervals and increased by 50-W increments until exhaustion. During these tests, blood was sampled from a hyperemized earlobe for lactate and pH measurement (and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
3
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 0 publications
1
32
3
3
Order By: Relevance
“…Lactic acid arises from the anaerobic metabolism of glucose or glycogen during high-intensity exercise and has been reported to decrease exercise performance when it has accumulated in muscles, for example by inhibiting muscle contraction. 16) The metabolic effect of capsiate on increasing the endurance performance supports the notion of sparing muscle glycogen. The lower levels of serum lactic acid in the capsiateadministered mice than in the controls during exercise explain the sparing of muscle glycogen and the enhancement of endurance capacity.…”
Section: Discussionmentioning
confidence: 68%
“…Lactic acid arises from the anaerobic metabolism of glucose or glycogen during high-intensity exercise and has been reported to decrease exercise performance when it has accumulated in muscles, for example by inhibiting muscle contraction. 16) The metabolic effect of capsiate on increasing the endurance performance supports the notion of sparing muscle glycogen. The lower levels of serum lactic acid in the capsiateadministered mice than in the controls during exercise explain the sparing of muscle glycogen and the enhancement of endurance capacity.…”
Section: Discussionmentioning
confidence: 68%
“…The lactate threshold occurs in a range between 60 to 80% of the peak work rate, as determined by spectroscopic measurement during exhaustive progressive muscle exercises in several previous studies (Barstow et al 1994b;Marsh et al 1991;McCreary et al 1996;Schocke et al 2004a). Accordingly, two studies, determining pH and lactate concentrations in muscle via biopsy and blood analysis during progressive muscle exercise, detected a sudden increase in muscle and blood lactate concentrations at an exercise intensity of about 60% _ V O 2max (Chwalbinska-Moneta et al 1989;Knuttgen and Saltin 1972). A recent study reported a significant decrease in muscle pH at a peak work rate of about 66%, without an associated increase in PCr hydrolysis during isotonic incremental exhaustive plantar flexion exercises (Schocke et al 2004a).…”
Section: Discussionmentioning
confidence: 95%
“…Progressive or ramp muscle exercises are characterised by decreases in pH with a significant descent at peak work rates ranging between 60 and 80% (Barstow et al 1994b;Chwalbinska-Moneta et al 1989;Knuttgen and Saltin 1972;Marsh et al 1991). Several previous 31 P-MRS investigations have shown that the linearity between PCr hydrolysis and workload is impaired when the pH in the muscle tissue falls below this so-called intracellular threshold, resulting in an acceleration of PCr hydrolysis via a pH-dependent impairment of creatine kinase activity (Barstow et al 1994b;Marsh et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Other indirect methods to estimate such thresholds use pulmonary gas exchange data (40, 49) (i.e., ventilatory threshold) or electromyographic signals (40). Several studies have aimed to compare different methods to determine the lactate and ventilatory thresholds using different protocols (9,11,35,40), although it is difficult to draw conclusions, as the results heavily depend on the specific methodologies used (e.g., cycle or treadmill, duration of exercise stage, blood sampling site). Others have attempted to investigate the relationship between lactate or ventilatory threshold and exercise performance in thermoneutral conditions (6,19,50).…”
mentioning
confidence: 99%